The war administration of Alexander Randall - Brown, Reuben Samuel Tilden (My University, 1921)
Contents include: the general condition of Wisconsin prior to the Civil War, Randall's first administration, the organization of war machinery, and Randall's administration of social relief.
[v], 29 leaves ; 29 cm.